Effects of Different Fertilizers with Potassium and Magnesium on the Yield and Quality of Potato - ZENGIN, M.; GOKMEN, F.; GEZGIN, S.; CAKMAK, I. (Asian Journal of Chemistry, 2010)
Potato (Solanum tuberosum var. Granola) were grown in trials of 15.15.15, gypsum, kieserite, potassium sulphate, kalimagnesia and ammonium sulphate materials in two locations of Nevsehir and Nigde provinces in 2005 and 2006 years. According to the results, in every two years in all locations effects of fertilizers used on tuber yields, tuber size distribution, dry matter content of tuber and K, Mg and S contents of leaves were significant changing depend on the locations. An important relation between K, Mg and S nutrition of plant and tuber yields were found in all locations. In two years, tuber yields obtained in all locations increased changing ratios between 2.4 and 132.9 % by fertilizer treatments with K, Ca, Mg and S by the side of N and P according to control treatment contained only N and P. In every two years, in all locations the highest tuber yield was obtained by treatment 6 having CAN + DAP + kalimagnesia + urea fertilizers that were given 650 kg N, 120 kg K2O, 68 kg S and 40 kg MgO per ha and treatment 5 having CAN + DAP + potassium sulphate + urea followed to this. At the same time, tuber yield having < 35 mm size decreased in ratio of 22.9 % as mean of all locations in treatment 6 according to control.